Influencia de la deficiente participación de los trabajadores en el clima laboral en la empresa globokas peru sac, en el año 2014. - Malca Seminario, Yasmin Madeleine (2015)
This research was the subject of study "POOR INFLUENCE OF EMPLOYEES IN THE WORK ENVIRONMENT IN THE COMPANY Globokas PERU SAC, in 2014"; the sample which was 70 workers intervened. The techniques used were: observation, structured interview, survey and bibliography. Therefore it aims to publicize as poor participation is affecting the working environment of the employees of the company Globokas. CHAPTER I It shows a theoretical framework on the problematic reality of poor participation of workers. CHAPTER II Academic justification, formulation of the problem, hypothesis, objectives, methods and techniques and the sample which intervened arises. CHAPTER III The interpretation of presentation of the results obtained from data collected during the research development through the on slopes (test) applied to employees of the company Globokas occurs. CHAPTER IV Response data and results produced by the survey, with a discussion of results. CHAPTER V Finally conclusions and recommendations on this work, literature and relevant annexes shown.